The image of the father in the autobiographical prose of A.P. Keshokov - Inna A., Kazharova (Kavkazologiya, 2022)
The subject of analysis in the present article is the ways of depicting the father in the autobio-graphical works of A.P. Keshokov - in the story «View from the White Mountain» and the story «Whose stirrup we held». The goal is to trace how the ways of displaying a particular personality inform about its value orientations, and how the differences in the ways of its depiction on differ-ent artistic canvases show a change in the value orientations of the artist himself. The compari-sons made allow us to say that in the story «View from the White Mountain» the author touches upon the events from the biography of Pshemakho Keshokov only tangentially. Having presented a detailed exposition of his father’s life in the chapter «Surname», the author deviates from it only once. In contrast to the story, a short biographical segment, recreated in the story «Whose stirrup we held», rearranges several value accents in the father’s story, to show the tragedy of his life. In the story, the «Islamic» theme sounds differently, the picture of Pshemakho Keshokov’s old age appears differently, his fate fits into a different value range - where the names of Pshikan She-kikhachev, Tuta Borukaev, Ibragim Tligurov sound. The years of publication of both works give grounds for conclusions about the value orientations of the writer.